Primary Au prospecting results in the Logrosán area (Central Iberian Zone, Spain). - Cheremazova, Ekaterina; Skublov, Sergey; Novoselov, Konstantin; Mikhailov, Alex; Galankina, Olga; Alexeev, Viktor (Journal of Iberian Geology, 2015)
The Central Iberian Zone presents an exceptional geological interest for its great exploration potential for a number of elements including gold. Metallogeny within the area is mainly related to regional metamorphism and late magmatic activity during the Variscan orogeny. In 2013-2014 junior company Mineral Exploration Network Ltd. has carried out an extensive prospecting field work with a primarily view to discover Au within the area around Logrosan granitic pluton (Cáceres, Spain). The main output of the survey was a localization and presorting of potentially mineralized territory unites at the extensive spatial scale (more than 240 sq. km). The known gold showings in the Central Iberian zone are considered to be synorogenic with a mainly metamorphic fluid source. As arsenic commonly forms widespread geochemical haloes near practically all orogenic gold deposits and appears to be easily and credibly measured by express analytical methods (XRF), it was selected as one of the major pathfinder elements for the initial prospecting. Designed geochemical survey allowed delineating potential target area with contrastive complex As-W-Zn-Pb anomaly in soil sediments and significant quantities of gold particles in heavy mineral concentrates. Placer gold particles analyses and their typomorphic features confirmed nearby primary gold source existence. The suggested scope of work proved to be efficient for assessing mineralization potential and selecting perspective target areas for a detailed drilling.
Keywords: gold exploration; Central Iberian Zone; pan concentrate; geochemical soil sampling; Iberian Variscan Belt